Other ruralities, between complementarity and differentiation from urbanization (Huellas, 2025)
In Argentina, the definition of rural space was created previous to the constitution of the National Statistical System as a dichotomous vision with respect to urban space. At present, this notion, anchored to the limit of the 2,000 inhabitants, is being revised in order to show how complex, diffuse, heterogeneous and multiple the rural space can be with its varied ruralities. Thus, the aim is to overcome the typologies based on one or two variables, and to account for the social construction of the space, the territory used by the actors and the place inhabited. The objective is to contribute to the theoretical and empirical delimitation of ruralities in the Southeast Buenos Aires by considering the following criteria: population density, the uses and coverings of land and accessibility. To achieve this, the concept of rurality in light of the review of specialized bibliography in the subject and the construction of an index of ruralities applied to the southeast of the province of Buenos Aires. As a result, three territorial categories were obtained: traditional, vanishing and contact ruralities.